An investigation into the key determinants of university–industry links in Algeria. (1st June 2015) - Boutifour, Zohra; Saad, Mohammed; Guermat, Cherif
The role of higher education institutions (HEIs) in developing the innovative capacity of societies is well recognized. As the main producers of knowledge, they contribute directly and indirectly to economic growth. Yet, little is known on the engagement of universities in developing countries with their social and economic environment. This article adopts a quantitative approach to identify the main factors affecting the role of Algerian HEIs in promoting and cooperating with their economic and social environment.